Critical Leadership Theory Integrating Transdisciplinary Perspectives - Chandler, Jennifer L.S (Springer International Publishing, 2018)
This book contributes five novel tenets for building a critical theory of leadership studies. Drawing from transdisciplinary insights, these tenets help shape the emerging field of inquiry. They also facilitate the examination of normative social processes that reinscribe hegemonic power relations - because much of what is accomplished in current leadership scholarship, teaching, and practice reinforces these power relations. The book begins by contrasting critical theory with positivist approaches to analyzing social phenomena, and what follows is an exploration of four broad disciplines using sub-components of leadership as an investigatory lens. The resulting five tenets are presented and discussed so that they may be picked up and used by scholars contributing to the developing field of critical leadership studies.